"When the Fun Stops, Stop": An analysis of the provenance, framing and evidence of a 'responsible gambling' campaign. - May Ci van Schalkwyk (Public Library of Science (PLoS), 2021)
When the Fun Stops, Stop, is a prominent 'responsible gambling' campaign in the UK, originally funded and delivered by the industry-initiated and funded Senet Group. Since the Senet Group's dissolution in 2020, the campaign has been overseen by the Betting and Gambling Council (BGC), the main gambling industry trade body. There has been no prior analysis of the activities, ideas and framing adopted by the Senet Group, who claimed to be acting as an industry 'watchdog' and oversaw what they characterised as a major public education campaign. We collated written and image-based material related to the Senet Group and its When the Fun Stops, Stop campaign from multiple sources. Guided by Entman's four functions of framing, we analysed the Senet Group's framing of the issues it sought to address, particularly harmful gambling, as well as its causes, and the solutions, focusing on the group's main activity: the delivery of the When the Fun Stops, Stop campaign. We also critically appraised an evaluation of the campaign funded by the Senet Group, using the findings to interrogate the stated claims about the campaign's effectiveness. The analysis showed that the Senet Group's framing of the problem, its causes, and proposed responses resemble those adopted by other industries and industry-funded groups. This involves portraying any harms caused by their products as limited to an atypical minority, rejecting upstream determinants of harm, and promoting individually-targeted voluntary measures, all contrary to the evidence of what works in health promotion, and what would characterise a public health approach. Neither the existing evidence base nor the evidence presented by the Senet Group support their claims about the campaign's effectiveness. These findings add to concerns about industry-funded campaigns in other areas. To minimise conflicts of interest, interventions intended to address gambling-related harms, such as public education campaigns, should be evidence-based and developed, implemented and evaluated completely independent of the industry and industry-funded organisations.